First results from five multidisciplinary diagnostic centre (MDC) projects for non-specific but concerning symptoms, possibly indicative of cancer - Chapman, D. (Br J Cancer, 2020)
BACKGROUND: Patients with non-specific symptoms often experience longer times to diagnosis and poorer clinical outcomes than those with site-specific symptoms. This paper reports initial results from five multidisciplinary diagnostic centre (MDC) projects in England, piloting rapid referral for patients with non-specific symptoms. METHODS: The evaluation covered MDC activity from 1st December 2016 to 31st July 2018, with projects using a common dataset. Logistical regression analyses were conducted, with a diagnosis of any cancer as the dependent variable. Exploratory analysis was conducted on presenting symptoms and diagnoses of cancer, and on comparisons within these groupings. RESULTS: In total, 2961 patients were referred into the MDCs and 241 cancers were diagnosed. The pathway detected cancers across a broad range of tumour sites, including several rare and less common cancers. An association between patient age and cancer was identified (p < 0.001). GP ‘clinical suspicion’ was identified as a strong predictor of cancer (p = 0.006), with a reduced association with cancer observed in patients with higher numbers of GP consultation before referral (p = 0.008). CONCLUSIONS: The MDC model diagnoses cancer in patients with non-specific symptoms, with a conversion rate of 8%, demonstrating the diagnostic potential of a non-site-specific symptomatic referral pathway.